2010
DOI: 10.1038/ismej.2010.153
|View full text |Cite
|
Sign up to set email alerts
|

Phage-induced lysis enhances biofilm formation in Shewanella oneidensis MR-1

Abstract: Shewanella oneidensis MR-1 is capable of forming highly structured surface-attached communities. By DNase I treatment, we demonstrated that extracellular DNA (eDNA) serves as a structural component in all stages of biofilm formation under static and hydrodynamic conditions. We determined whether eDNA is released through cell lysis mediated by the three prophages LambdaSo, MuSo1 and MuSo2 that are harbored in the genome of S. oneidensis MR-1. Mutant analyses and infection studies revealed that all three prophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
191
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(207 citation statements)
references
References 76 publications
(99 reference statements)
15
191
1
Order By: Relevance
“…Spontaneous SV1-mediated cell lysis was shown to occur in S. pneumoniae, and, accordingly, deletion of the SV1 phage lysin led to a decrease in cell lysis, eDNA release, and biofilm formation (69). In S. oneidensis, three prophages, MuSo1, MuSo2, and LambdaSo, jointly affect lysis and eDNA release, and consequently, a mutant devoid of all three phages is severely impaired in all stages of biofilm formation (70). Recent studies on this species have demonstrated that environmental iron levels are an important factor involved in inducing expression of LambdaSo in a RecA-dependent fashion during biofilm formation (71).…”
Section: Phages Affect Microbial Biofilm Formationmentioning
confidence: 99%
“…Spontaneous SV1-mediated cell lysis was shown to occur in S. pneumoniae, and, accordingly, deletion of the SV1 phage lysin led to a decrease in cell lysis, eDNA release, and biofilm formation (69). In S. oneidensis, three prophages, MuSo1, MuSo2, and LambdaSo, jointly affect lysis and eDNA release, and consequently, a mutant devoid of all three phages is severely impaired in all stages of biofilm formation (70). Recent studies on this species have demonstrated that environmental iron levels are an important factor involved in inducing expression of LambdaSo in a RecA-dependent fashion during biofilm formation (71).…”
Section: Phages Affect Microbial Biofilm Formationmentioning
confidence: 99%
“…Notably, eDNA is not only a valuable nutrient for Shewanella and other species (41). We have recently demonstrated the presence of significant amounts of eDNA in S. oneidensis MR-1 biofilms, which are thought to be released by prophage-induced cell lysis (23). We demonstrated that treatment with DNase I strongly decreases the ability of S. oneidensis MR-1 to attach to a surface initially and that the subsequent formation of 3-dimensional structures is severely affected.…”
mentioning
confidence: 98%
“…it is believed that prophages in the bacterial genome are important for biofilm development because of the release of extracellular DNA on cell lysis. [52] Other nucleotides (e.g. ATP, GTP and AMP) In addition to DNA and RNA several other nucleotides have been identified in aquatic environments (Fig.…”
Section: Quantificationmentioning
confidence: 99%
“…DNA is an important structural component of the extracellular polymer matrix of biofilms. [51][52][53] For V. cholera extracellular DNA is implicated in the development of biofilm architecture, nutrient acquisition and biofilm detachment. [53] For Shewanella sp.…”
Section: Quantificationmentioning
confidence: 99%